Distribuição espaço-temporal de borboletas frugívoras em ambientes tropicais sazonais - Marina do Vale Beirao (2016)
1. Tropical dry forests are among the most threatened and neglected habitats in the world. In Brazil, they are naturally fragmented and embedded within various biomes. Thus, it is important to determine if insect communities are homogeneous among geographically separated dry forest fragments. 2. This study quantified the diversity and structure of fruit-feeding butterfly communities in four dry forest sites in northern and central Minas Gerais, Brazil by sampling 7,732 individuals belonging to 48 species. 3. Differences in butterfly community structure were found between northern and central Minas Gerais. Although species richness per plot was the same in both areas, abundance per plot was higher in northern sites than in the central site, and species composition differed between sites. Additive partitioning showed that beta diversity corresponded to 70.1% of all the diversity. Beta diversity primarily represented species turnover per se, rather than species loss, and it was potentially driven by differences in the habitat types surrounding the sites, and their evolutionary histories. Butterfly community composition and abundance were influenced by vegetation type and structure present at each site. Predictably, butterfly species richness and abundance were higher in the wet season than in the dry season. 4. The difference in butterfly community structure across relatively short geographic distances highlights the importance of conserving tropical dry forest fragments to ensure the maintenance of the diversity of butterflies and, presumably, other insects.